Our feature presentation strategy - Champoux, Joseph E. (Thomson higher Education, 2006)
Discusses various human resource management topics through selected scenes from various films. This work combines a workbook with actual film clips. It provides students with a visual portrayal of abstract human resource management concepts, giving HRM both relevance and context. It discusses various aspects of film such as editing, and sound.